2006
DOI: 10.1002/mawe.200600059
|View full text |Cite
|
Sign up to set email alerts
|

Mechanische und tribologische Eigenschaften von hochstickstoffhaltigen Austeniten

Abstract: Austenitic stainless steels provide a fair combination of strength, toughness and corrosion resistance. Undergoing tribological stresses -in particular under self-mating contact situations -their performance is not sufficient. Thus the more wear resistant austenitic Co-base alloys with different carbon contents are applied under these circumstances, which may prevail in medical applications. Austenitic high-Nitrogen Steels might be an alternative under these circumstances. Strength, corrosion resistance and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, Rigney and Glaeser (1978) and Rigney (2000) has shown by large-scale molecular dynamics simulations of sliding that with the right extent of strain rate a nano-crystalline structure will be produced. Fischer et al (2006) have shown that the formation of this nano-crystalline structure together with a low stacking fault energy are the key factor for the great wear performance of this cobalt-chromium alloy. The production of wear debris takes only place in this layer of nano-crystals with the result of nanometer-sized wear particles and an overall lower volumetric wear rate.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Rigney and Glaeser (1978) and Rigney (2000) has shown by large-scale molecular dynamics simulations of sliding that with the right extent of strain rate a nano-crystalline structure will be produced. Fischer et al (2006) have shown that the formation of this nano-crystalline structure together with a low stacking fault energy are the key factor for the great wear performance of this cobalt-chromium alloy. The production of wear debris takes only place in this layer of nano-crystals with the result of nanometer-sized wear particles and an overall lower volumetric wear rate.…”
Section: Discussionmentioning
confidence: 98%